Endodontic Management of Three Rooted Mandibular First Molar: Report of Three Cases - Acharya, N; Samant, PS; Gautam, V; Singh, O; Shrestha, A (Journal of Universal College of Medical Sciences, 2014)
In everyday endodontic practice, clinicians face various atypical configurations, such as presence of extra root and/or atypical canal configuration. One of the major reason of the treatment failure is the missed extra root and/or canals. Mandibular first molars typically have two roots (one mesial and one distal), but sometimes present with a supernumerary root either distolingually (radix entomolaris), or mesiobuccally (radix paramolaris). Hence, the thorough knowledge of root canal anatomy and morphology along with its variation is crucial for the successful outcome of the root canal treatment. The aim of this paper is to present and describe the three clinical case reports of three rooted mandibular first molars and its endodontic management. DOI: http://dx.doi.org/10.3126/jucms.v2i2.11173 Journal of Universal College of Medical Sciences (2014) Vol.2(2): 40-45